Intellectual Capital: A Focus on Human Capital Reporting Practices of Top Malaysian Listed Companies - Husin, Norhayati Mat; Ahmad, Noormala; Sapingi, Raedah (The South East Asian Journal of Management, 2011)
This paper aims to examine the extent of human capital (HC) reporting among top Malaysian companies and introduce an HC reporting guideline that can be used by Malaysian companies and regulator. It begins by developing the HC framework based on previous intellectual capital (IC) frameworks. This framework is then used to examine each of the top 100 Malaysian companies listed on the Bursa Malaysia in year 2008. Using the content analysis method, it reviews the annual reports of these companies to determine the extent of HC reporting. The findings of this paper highlight the need for the development of IC framework particularly on HC. HC differences were also identified between Malaysia and other countries such as Sri Lanka and Australia, and it is argued that these differences can be attributed to the social, economic, and political factors.